(untitled) (Research, Society and Development, 2021)
Search the literature for activities performed by family caregivers to people with Parkinson’s disease, pointing out their main difficulties and activities implemented at home to improve the patient’s quality of life. This is an integrative literature review, with a descriptive and qualitative aspect. The search for data took place in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS); Scientific Electronic Library Online (SciELO) and Nursing Database (BDENF). The research took place from June to July 2021, and the descriptors “Parkinson’s Disease; Caregivers; Home care”. Established in the list of Health Sciences Descriptors (DECs), and after applying the eligibility criteria, eight studies remained to be used in the study. The main difficulty in home care for patients with PD is the lack of information about the pathology and, consequently, the lack of preparation of caregivers, who are mostly composed of female spouses. It is concluded that it is necessary to have an effective health promotion in the home context, to offer qualification and preparation to these informal caregivers.